Improve Critical Thinking by Developing Teaching Materials Based on Realistic Mathematics Learning - Muhammad Farid Nasrulloh; Wardatul Fuadah Amin (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The research aim of this study are (1) to determine the development of mathematics teaching materials based on Realistic Mathematics Learning approach (RML) to improve students critical thinking skills. (2) To determine the feasibility of teaching materials to improve students critical thinking. (3) To determine the improvement of teaching materials in students critical thinking skills. This type of research is development research. The development model refers to the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The study was carried out on class VIIID MTs Al-Ihsan Kalikejambon Tembelang Jombang in the 2020/2021 academic year. The results obtained that the average media validity score based on the Realistic Mathematics Learning approach on the material of Statistics class VIII from the experts, namely mathematics lecturers, was 72,4% which was categorized as quite valid, and mathematics teachers were 80,6% which was categorized as valid. Practicality is obtained based on the results of observational data on the implementation of teaching materials based on Realistic Mathematics Learning, obtained an average of 69,4% which is in the fairly good category. The effectiveness is obtained from the results of questionnaires on student responses and student learning outcomes. An average of 91,67% was obtained from the data from student questionnaires who were in the good category, for each aspect that was responded to. As many as 81,3% of students were able to achieve the criteria of complete learning so that the Realistic Mathematics Learning-Based Learning media was categorized as effective.